A survey on the teaching of English reading skills to the first year students in mixed ability classes at Vietnam Forestry Universtiy - Hồ, Thị Xuân Hồng (University of Languages and International Studies, 2017)
Part A is the introduction which states the rationale, aims, scope, method, significance and organization of the study. Part B is the development which consists of 4 chapters: Chapter 1, which serves as a theoretical and methodological foundation of the study reviews the literature relevant to the topic. Chapter 2 presents the research methodology. Chapter 3 refers to the results and discussion of the survey in addition to the summary of the main findings. Chapter 5 is the implications which include some suggestions for better teaching and learning reading to the first year students in MAC in VFU. Part C is the conclusion that summarizes what has been done through the study, presents the limitations and gives some suggestions for further researches.